Purification of Electron-Transferring Flavoprotein from Megasphaera elsdenii and Binding of Additional FAD with an Unusual Absorption Spectrum - Sato, Kyosuke; Nishina, Yasuzo; Shiga, Kiyoshi (Journal of biochemistry (Tokyo), 2003)
Electron-transferring flavoprotein (ETF), its redox partner flavoproteins, i.e., d-lactate dehydrogenase and butyryl-CoA dehydrogenase, and another well-known flavoprotein, flavodoxin, were purified from the same starting cell paste of an anaerobic bacterium, Megasphaera elsdenii. The purified ETF contained one mol FAD/mol ETF as the sole non-protein component and bound almost one mol of additional FAD. This preparation is a better subject for investigations of M. elsdenii ETF than the previously isolated ETF, which contains varying amounts of FAD and varying percentages of modified flavins such as 6-OH-FAD and 8-OH-FAD. The additionally bound FAD shows an anomalous absorption spectrum with strong absorption around 400 nm. This spectral change is not due to a chemical modification of the flavin ring because the flavin released by KBr or guanidine hydrochloride is normal FAD. It is also not due to unknown small molecules because the same spectrum appears when ETF is reconstituted from its guanidine-denatured subunits and FAD. A similar anomalous spectrum was observed for AMP-free pig ETF under acidic conditions, suggesting a common flavin environment between pig and M. elsdenii ETFs.